Risk Factors for Obstructive Sleep Apnea Are Prevalent in People with Psychosis and Correlate with Impaired Social Functioning and Poor Physical Health - Liu, Dennis; Myles, Hannah; Foley, Debra L.; Watts, Gerald F.; Morgan, Vera A.; Castle, David; Waterreus, Anna; Mackinnon, Andrew; Galletly, Cherrie Ann (Frontiers in Psychiatry, 2016)
Background: Obstructive sleep apnoea (OSA) in the general community is associated with obesity, smoking, alcohol and sedative medication use; and contributes to depressed mood, daytime sedation, and sudden cardiovascular deaths. Poor cardiovascular health, impaired social functioning, negative and cognitive symptoms are also among the common clinical features of psychotic disorders. People with psychosis have higher rates of sleep disturbance, however, OSA has not been extensively investigated in this population. Aims: This study aimed to determine the prevalence of OSA and general sleep disruption symptoms in a representative Australian sample of people with psychosis. We investigated the prevalence of potential risk factors for OSA including obesity, psychotropic medications, and substance abuse in this population. Finally, we evaluated associations between symptoms of OSA, symptoms of general sleep disruption, and various clinical features in people with psychosis. Methods: Participants took part in the Second National Australian Survey of Psychosis, a population-based survey of Australians with a psychotic disorder aged 18-64 years. Symptoms associated with OSA (snoring and breathing pauses during sleep) in the past year were assessed using questions from the University of Maryland Medical Centre Questionnaire, and symptoms associated with general sleep disruption in the past week using the Assessment of Quality of Life Questionnaire (AQoL). Data collected included psychiatric diagnosis and symptoms, education, employment, medications, smoking status, physical activity, drug and alcohol use, and cognitive function. Physical health measures included body mass index, waist circumference, blood pressure, fasting blood glucose and lipids. Results: Snoring was reported by 41.9%; 7% stating they frequently stopped breathing (pauses) during sleep. Univariate logistic regressions show OSA symptoms (pauses and snoring) were associated with older age, female gender, lower levels of social participation or employment, cardiovascular risk factors, sedentary lifestyle and poorer quality of life, whilst symptoms of general sleep disruption were more likely in people with depressive symptoms. Conclusions: Australians with psychosis have high levels of sleep disturbance including OSA. OSA symptoms were associated with cardiovascular disease risk factors, reduced social participation and employment, and poorer quality of life. Whether correction of OSA can improve these factors in people with psychosis remains to be determined.